Teacher's Exemplary Approach to Shaping the Discipline Character of Students at SMK Negeri 2 Gowa - Husma, Husma; Haris, Hasnawi; Mustari, Mustari; Nasuhan, Najamuddin (JED (Jurnal Etika Demokrasi), 2025)
The challenge of declining student exemplary and discipline values, especially at the vocational school level, encourages the need for a new approach to learning. This study aims to explore the effectiveness of the teacher's exemplary approach in shaping the disciplinary character of students at SMK Negeri 2 Gowa. The research uses a qualitative method with case studies. Data were collected through observation, interviews, and documentation, then analyzed descriptively. The results showed that teachers' exemplary behavior in time, task, and attitude significantly influenced students' disciplinary behavior. This research highlights the importance of the role of teachers as models in character education.